HIF-1/2α-Activated RNF146 Enhances the Proliferation and Glycolysis of Hepatocellular Carcinoma Cells via the PTEN/AKT/mTOR Pathway - Shen, Guoliang; Wang, Hao; Zhu, Ning; Lu, Qiliang; Liu, Junwei; Xu, Qiuran; Huang, Dongsheng (Frontiers in Cell and Developmental Biology, 2022)
Hypoxia microenvironment, a critical feature of hepatocellular carcinoma, contributes to hepatocarcinogenesis, tumor progression and therapeutic resistance. Hypoxia-inducible factors (HIFs)-activated target genes are the main effectors in hypoxia-induced HCC progression. In this study, we identified ubiquitin E3 ligase ring finger protein 146 (RNF146) as a novel HIFs target gene. Either HIF-1α or HIF-2α knockdown significantly repressed hypoxia-induced RNF146 upregulation in Hep3B and Huh7 cells. TCGA data and our immunohistochemistry analysis consistently revealed the overexpression of RNF146 in HCC tissues. The upregulated expression of RNF146 was also detected in HCC cell lines. The high RNF146 level was correlated with poor clinical features and predicted a shorter overall survival of patients with HCC. RNF146 knockdown suppressed the proliferation, colony formation and glycolysis of HCC cells, but suppressed but RNF146 overexpression promoted these malignant behaviors. Moreover, RNF146 silencing weakened HCC growth in mice. RNF146 inversely regulated phosphatase and tensin homolog (PTEN) protein level, thereby activating the AKT/mechanistic target of rapamycin kinase (mTOR) pathway in HCC cells. MG132 reversed RNF146 overexpression-induced PTEN reduction. RNF146 knockdown decreased the ubiquitination and degradation of PTEN in HCC cells. Therefore, we clarified that PTEN knockdown notably abolished the effects of RNF146 silencing on the AKT/mTOR pathway and Hep3B cells’ proliferation, colony formation and glycolysis. To conclude, our data confirmed that RNF146 was transcriptionally regulated by HIF-1/2α and activated the AKT/mTOR pathway by promoting the ubiquitin proteolysis of PTEN, thereby contributing to HCC progression. RNF146 may be a potential new drug target for anti-HCC.